Análise da atividade das psicólogas de CRAS do vale do Sabugi-PB - Medeiros, Luann Glauber Rocha (2015)
This work has as main objective to carry out an analysis of psychologists activity Social Assistance Reference Centers - CRAS the cities of the micro-region of the Paraíba Valley Sabugi call. The actions promoted by CRAS these cities are of great importance to maintaining a social welfare and social and economic promotion of families in vulnerable situations. It is of great importance to understand the work of the technical staff of these CRAS. The study included four psychologists who work in the five cities that make up the aforementioned micro-region of the state, and one of these psychologists working in two cities, with ages ranged between 24 and 36 years, with experience times ranging from six months to 10 years. From a theoretical point of view, this study made use of the knowledge arising from the Ergonomic of the activity, the Psychodynamics of work and Ergology. The method employed is a non-experimental design of qualitative nature, combining semi-structured interviews and observations in the workplace. For analysis, we used the content analysis feature by building themes, being established four categories of analysis. The known risks and working conditions, shows deficits in terms of infrastructure and what the risks faced by respondents in developing its activity, both social and in terms of transport, among others. In the second phase, this was the task and activity of the psychologists themselves, showing they report that their activities permeate from the individual attention to technical and bureaucratic activities. In the third category, the training was discussed, which is insufficient for the performance of them in the CRAS, which is reflected in the activity of the interviewees. Finally, it addressed the question of recognition, which, according to them, is given more by users than by management.